Observers use facial masculinity to make physical dominance assessments following 100‐ms exposure. Issue 2 (26th November 2020) - Albert, Graham; Wells, Erika; Arnocky, Steven; Liu, Chang Hong; Hodges‐Simeon, Carolyn R.
Abstract: Research has consistently demonstrated that faces manipulated to appear more masculine are perceived as more dominant. These studies, however, have used forced‐choice paradigms, in which a pair of masculinized and feminized faces was presented side by side. These studies are susceptible to demand characteristics, because participants may be able to draw the conclusion that faces which appear more masculine should be rated as more dominant. To prevent this, we tested if dominance could be perceived when masculinized or feminized faces were presented individually for only 100 ms. We predicted higher dominance ratings to masculinized faces and better memory of them in a surprise recognition memory test. In the experiment, 96 men rated the physical dominance of 40 facial photographs (masculinized = 20, feminized = 20), which were randomly drawn from a larger set of faces. This was followed by a surprise recognition memory test. Half of the participants were assigned to a condition in which the contours of the facial photographs were set to an oval to control for sexual dimorphism in face shape. Overall, men assigned higher dominance ratings to masculinized faces, suggesting that they can appraise differences in facial sexual dimorphism following very brief exposure. This effect occurred regardless of whether the outline of the face was set to an oval, suggesting that masculinized internal facial features were sufficient to affect dominance ratings. However, participants' recognition memory did not differ for masculinized and feminized faces, which could be due to a floor effect.